2018
DOI: 10.1152/ajprenal.00596.2017
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine-1-phosphate pathway in renal fibrosis

Abstract: Renal fibrosis is defined as the excessive deposition and modification of extracellular matrix (ECM) in the renal parenchyma in response to injury and inflammation, resulting in renal function loss. This condition is common to many chronic kidney diseases occurring under diverse pathological conditions, such as diabetic and hypertensive nephropathy. Sphingosine-1-phosphate (S1P) is a bioactive sphingolipid metabolite involved in the regulation of cardiovascular functions and the pathogenesis of various cardiov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 55 publications
0
24
0
Order By: Relevance
“…Recent studies support an important role for S1P in renal diseases, including renal fibrosis (reviewed in Ref. [ 54 ]), nephrotic syndrome [ 8 , 9 ] and other glomerular diseases such as IgA nephropathy and lupus nephritis [ 55 , 56 ]. Early studies of streptozotocin (STZ)-treated rats revealed increased levels of S1P in isolated glomeruli during initial stages of DKD [ 57 ].…”
Section: Sphingolipid Signaling In Glomerular Diseasementioning
confidence: 99%
“…Recent studies support an important role for S1P in renal diseases, including renal fibrosis (reviewed in Ref. [ 54 ]), nephrotic syndrome [ 8 , 9 ] and other glomerular diseases such as IgA nephropathy and lupus nephritis [ 55 , 56 ]. Early studies of streptozotocin (STZ)-treated rats revealed increased levels of S1P in isolated glomeruli during initial stages of DKD [ 57 ].…”
Section: Sphingolipid Signaling In Glomerular Diseasementioning
confidence: 99%
“…The explanation for this discrepancy could be the different selectivity in S1P receptors between S1P and the agonist FTY720 used in the above study. The FTY720 does not act on S1PR2 [47], whereas the S1PR2-mediated signaling has been shown to play a very important role in the kidney damage [15,48]. The renal protection by SphK1 KO in the present study is probably through the inhibition of S1PR2-mediated signaling when S1P level is reduced.…”
Section: Discussionmentioning
confidence: 47%
“…One of the significant effects by S1P is its role in fibrosis as evidence shows interaction between S1P signaling and TGF-β1 signaling to form a vicious cycle in fibrosis [15]. Fibrotic genesis is the crucial pathological process in chronic kidney diseases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enrichment analysis showed that the genes in module 1-4 were mainly associated with type I interferon signaling pathway, fibrinolysis, and extracellular matrix organization, specifically inflammatory response and immune response in cluster rank 4 ( Table 1). Previous studies have reported these GO terms to be related to kidney or tubular epithelial cell damage [19,20]. Therefore, genes included in the four clusters were more suspectable to participate in the triggering of injury mechanism of renal tubule-interstitium compared to other DEGs.…”
Section: Integration Of Protein-protein Interaction (Ppi) Network Andmentioning
confidence: 89%